Dampak Penggunaan Gadget terhadap Perkembangan Psikologi pada Anak Sekolah Dasar - Suardana, Dewa Nyoman; Suarni, Ni Ketut; Margunayasa, I Gede (Universitas Batanghari Jambi, 2025)
This research aims to investigate the effects of gadget use on the psychological development of elementary school-aged children. The method used is a qualitative approach. This approach was selected to master the natural conditions of the research object, and data collection methods through triangulation (observation, interviews, documentation). The results of the study concluded that there was an influence of the duration of gadget use on the mental, emotional and behavior of children in elementary school. The positive influence that arises, for example, broadens students' insight and makes it easier for students to communicate with teachers. Meanwhile, the negative effects include difficulty socializing, irritability, imitating behavior on gadgets and addiction to playing with gadgets. So it is very important for parents to supervise, control and pay attention to all their children's activities.